Effectiveness of an Educational Program upon Nurses’ Knowledge about Complications Reduction at the Peritoneal Dialysis Units - Dergham M. Hameed (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The study aims at identifying the nurses’ knowledge about peritoneal dialysis complications, to construct an education program for nurses in peritoneal dialysis units, to determine the effectiveness of the education program upon the nurses’ knowledge about complications of peritoneal dialysis, and to identify the relationship between the nurses’ knowledge and their demographic characteristics of level of education and years of experience. Methodology: A quasi-experimentai study was carried out at the peritoneal dialysis units of Baghdad teaching hospitals, from April 2004 to April 2006. ٨ purposive sample of (50) nurse was selected from Baghdad teaching hospitals. These nurses working at the peritoneal dialysis units to provide nursing care for a patient who has undergone peritoneal dialysis. The data were collected through the use of constructed questionnaire, which comprised of (56) item distributed in (7)sections. The reliability of the instrument was determined through test-retest and the validity through a panel study of experts. The data were analyzed through the application of descriptive statistical analysis that included (frequency, mean, mean of scores, standard deviation, and percentage) and the application of inferential statistical analysis that included (test for independent sample, test for dependent sample pre-test and post-test, pearson correlation coefficient, Chi-square, and analysis of variance for the difference between pre-test, post-testi, and post-test2 of the study group). Results: The results of the study indicated that the education program had a positive impact on the knowledge of nurses in peritoneal dialysis units regarding peritoneal dialysis complications and significant association was identified between the nurses’ knowledge relation to their education level at the study group (pre-test). Recommendations: Based on the result of the study, the study recommended that Nurses who are working at the peritoneal dialysis unit should be encouraged to participate in education program and training session for their benefit of their practice in such units, in service continuing education program should be presented to nurse at the peritoneal dialysis unit on a regular base to maintain their level of knowledge.